Clinical and laboratory characterictic of acute HIV-infection in adult residents of Novosibirsk region - Ya. S. Ulyanova; N. M. Gashnikova; V. V. Ivlev; E. I. Krasnova; N. I. Khokhlova; A. V. Totmenin; O. V. Melnikova; M. V. Vorotova; I. R. Glushko; V. V. Ulyanov (Журнал инфектологии)
Purpose of the study. To study the characteristics of acute HIV infection in adults in the Novosibirsk region in 2017– 2018.Materials and methods. 200 patients with acute HIV infection, residents of the Novosibirsk region, aged 15 to 74 years, hospitalized in 2017–2018, 104 men and 96 women were examined. The diagnosis was verified by detecting antibodies to HIV in ELISA with a negative or doubtful result of the immunoblot, as well as by determining the quantitative content of HIV RNA in the blood by PCR. The hemogram, the content of CD4 + lymphocytes in the blood were determined. In addition, HIV-1 was studied in 71 patients for belonging to a genetic group.Results. Patients of 20–40 years old prevailed – 70.5%. The sexual way was dominant in women (69.0%), injecting psychoactive substances was more often in men (32.2%). Frequent symptoms were fever (99%), exanthema (65.5%), polylimfoadenopathy (54.0%). Less common were diarrhea (36.0%), pharyngotonsillitis (23.0%), aphthous stomatitis (6.5%), hepatomegaly or hepatosplenomegaly (8.5%). Secondary diseases were revealed in 26.5% of patients. Leukopenia was recorded in 63.0%, thrombocytopenia in 62.5%, lymphocytosis and atypical cells of the lymphoid series in 14.0%. All patients had a high “viral load” – from 23,000 to 10,000,000 or more copies / ml, a decrease in the number of CD4 + less than 350 cells – in 38.0%. From among 71 patients, 19.7% had HIV-1 subtype A, and 76.0% had recombinant HIV-1 CRF63_02A. In the latter, “viral load” of more than 10,000,000 copies / ml was more often recorded (67.8% vs. 33.4%, p = 0.004).Conclusion. A significant number of cases of acute HIV infection were reported in the Novosibirsk region in 2017– 2018. Its detection is possible by examination of all febrile patients who apply to medical institutions. Early initiation of antiretroviral therapy with the appointment of well-tolerated regimens contributes to the formation of a high commitment to therapy.